2004
DOI: 10.1021/ic0490223
|View full text |Cite
|
Sign up to set email alerts
|

Liberation of Pnicogen Chains from Cu2P1.8As1.2I2:  Synthesis and Characterization of a New Allotrope of P−As

Abstract: Removal of CuI from Cu(2)P(1.8)As(1.2)I(2) results in a novel P--As allotrope. Although the product is X-ray amorphous, lattice fringes are observed in the transmission electron micrographs with spacings reflecting the diameter of the linear pnicogen polymer in Cu(2)P(1.8)As(1.2)I(2), suggesting the pnicogen chains remain intact upon loss of CuI. The straight needles present in Cu(2)P(1.8)As(1.2)I(2) appear to be kinked in the P--As phase due to lattice mismatch between the liberated polymers, ultrasonic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
9
0
4
Order By: Relevance
“…[26] Allotropes of arsenic, similar to the various forms of red phosphorus, have not yet been studied extensively. So far, only mixed P-As chains ]X4(4)[X8] with up to 55 % As [12][13][14] together with violet phosphorus incorporating 5 % arsenic [15] have been prepared experimentally. Thus it might be reasonable to first focus on the synthesis of ring-shaped allotropes of phosphorus.…”
Section: Comparisons Between the Allotropes Of Arsenicmentioning
confidence: 99%
See 2 more Smart Citations
“…[26] Allotropes of arsenic, similar to the various forms of red phosphorus, have not yet been studied extensively. So far, only mixed P-As chains ]X4(4)[X8] with up to 55 % As [12][13][14] together with violet phosphorus incorporating 5 % arsenic [15] have been prepared experimentally. Thus it might be reasonable to first focus on the synthesis of ring-shaped allotropes of phosphorus.…”
Section: Comparisons Between the Allotropes Of Arsenicmentioning
confidence: 99%
“…After that, the techniques could be applied for As and mixed P-As rings. The copper halide matrix techniques used in several successful syntheses of phosphorus [9] and P-As chains [12][13][14] could be a starting point for the synthesis of the rings.…”
Section: Comparisons Between the Allotropes Of Arsenicmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that the pnicogen chains in both (CuI) 8 P 12 and (CuI) 8 P 7.2 As 4.8 can effectively be liberated from the CuI host by treatment with aqueous potassium cyanide, producing novel allotropes of phosphorus and binary P-As, respectively. [13,14] Although each pnicogen position in (CuI) 8 P 7.2 As 4.8 has shared occupancy of both P and As, the "roof" positions in the [Pn8] cages (indicated by * in Figure 1) appear to be As rich, suggesting that these are not true solid solutions, but that there are preferred sites for As within the structure. Furthermore, the Cu I lattice in the 40 % As phase shows increased disorder relative to the parent compound, suggesting that As substitution may lead to augmented copper ion conductivity.…”
Section: Planar Squaresmentioning
confidence: 99%
“…Recently, a mixed pnictogen analog, Cu 2 P 1.8 As 1.2 I 2 , with an unprecedented 40 % As substitution into the neutral chain, has been synthesized [4]. This new phase has a larger number of partially occupied copper sites relative to the parent compound, and some of the sites are located outside of a normal bonding distance to P/As.…”
Section: Introductionmentioning
confidence: 99%